Analysis and evaluation of mechanical performance of reinforced sandwich structures: X-CorTM and K-CorTM - Marasco, Andrea I. (Cranfield University, 2005)
X-CorTM and K-CorTM are foam based lightweight structural cores reinforced with ZFiber ® rods oriented in a truss pattern. They can generate sandwich structures which possess strength- and stiffness-to-weight ratios such to compete with aerospace grade honeycomb constructions. The enhanced tailoring ability to specific design needs, the flexibility in reinforcement type and arrangement, the variety between closed cell foamfilled or hollow core configurations for ultimate weight savings or structural multifunctionality, while utilising manufacturing procedures similar to traditional honeycomb sandwich structures (low cost out-of-autoclave manufacturing techniques included) make these novel materials an attractive alternative. The process of their implementation into current engineering practice requires a parallel comparison with existing competitor cores and a critical evaluation of their performance, identifying advantages and disadvantages. This study represents one of the first attempts to create a rigorous methodology for the analysis and evaluation of their mechanical behaviour and manufacturing sensitivities. The balance of out-of-plane properties (shear and compression), fundamental for a sandwich core material, has been investigated. The material energy absorption capacity for the aforementioned loading cases, as well as for in-plane crushing was evaluated. For this purpose, a new quasi-static test for progressive crushing of flat sandwich laminates was designed successfully. The experimental data gathered validate proposed analytical models which allowed further deductions on core parameters influence to be made. Those parameters were the pin insertion angle, pin lay-out, pin density and the role of the foam. A local-global FE modelling approach for Z-pinned sandwich cores is also provided and validated for X-CorTM structures. Structural differences between XCorTM and K-CorTM are at the base of a diverse mechanical response; their performance is sensitive to the manufacturing process, as it determines the quality of the pin-skin and pin-adhesive film interfaces. An ‘improved’ manufacturing technique designed for XCorTM resulted in a sandwich panel able to offer the same mechanical performance of a Nomex® honeycomb structure for a 25% of weight saving.